2007
DOI: 10.1159/000101066
|View full text |Cite
|
Sign up to set email alerts
|

Distinction of Neurochemistry between the Cores and Their Shells of Auditory Nuclei in Tetrapod Species

Abstract: The distribution of Met-enkephalin (ENK), substance P (SP) and serotonin (5-HT) differs between the core and shell regions of the mesencephalic and diencephalic auditory nuclei of the turtle [Belekhova et al., 2002]. These neurochemical distinctions are also found in other tetrapods (mammals, birds and amphibians). The distribution of ENK, SP and 5-HT was examined in the core and shell regions of both mesencephalic and diencephalic auditory nuclei, and in the telencephalic auditory areas of Bengalese finches (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 154 publications
(117 reference statements)
3
24
2
Order By: Relevance
“…The distribution of SERT-ir fibers was relatively homogenous across CMM and NCM, with clusters of fibers appearing to surround unlabeled cell bodies in some individuals. Whereas Zeng et al (2007) reported that MLd in Bengalese finches is nearly devoid of serotonergic fibers, we found that although it was less densely labeled than the surrounding nucleus intercollicularis, it was clearly innervated by SERT-ir fibers (Fig. 5B).…”
Section: Resultscontrasting
confidence: 63%
See 4 more Smart Citations
“…The distribution of SERT-ir fibers was relatively homogenous across CMM and NCM, with clusters of fibers appearing to surround unlabeled cell bodies in some individuals. Whereas Zeng et al (2007) reported that MLd in Bengalese finches is nearly devoid of serotonergic fibers, we found that although it was less densely labeled than the surrounding nucleus intercollicularis, it was clearly innervated by SERT-ir fibers (Fig. 5B).…”
Section: Resultscontrasting
confidence: 63%
“…With the exception of Ov, within which only the shell region contained appreciable labeled fibers (see also Belekhova et al, 2002; Kaiser & Covey, 1997; Zeng et al, 2007), the auditory structures we focused on for this study were densely innervated (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations